Review and prospect on key technologies of hydroelectric‐hydrogen energy storage‐fuel cell multi‐main energy system. Issue 2 (3rd November 2021) - Liu, Jiawei; Tang, Quan; Li, Min; Su, Yunche; Li, Ting
Abstract: Hydropower engineering is one of the most developed renewable energy generation techniques, which is characterized by high development concentration, large dispatching scale, many power stations, and long transmission distance. However, the unbalanced distribution of hydropower resources and the difficulty of absorbing hydropower lead to a large amount of abandoned water, which causes a large number of economic losses and energy loss in China. The topological structure and principle of the multi‐agent energy system of hydropower, hydrogen storage, and fuel cell are introduced here. The key technologies of the multi‐agent energy system are introduced from three parts: hydrogen production method of electrolysis water, hydrogen storage method, and application aspect of power generation system of solid oxide fuel cell. The main research direction of realizing the multi‐agent energy system of hydroelectric power, hydrogen energy storage, and fuel cell in the future is put forward, which has enlightenment significance for the construction of new power system and the research of realizing the goal of carbon neutral.